2022
DOI: 10.1007/s11033-022-07129-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of pathogenic variants in BRCA1 and BRCA2 genes using next-generation sequencing in women with triple negative breast cancer from South India

Abstract: The frequency of triple-negative breast cancer (TNBC) incidence varies among different populations, suggesting the involvement of genetic component towards TNBC development. Previous studies have reported that BRCA1/2 germline mutations confer a lifetime risk of developing TNBC. However, there is hardly any information regarding the common pathogenic variants (PVs) in BRCA1/2 genes that contribute to TNBC in the Indian population. Hence, we screened for PVs in BRCA1/2 and their association with clinico-patholo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 54 publications
2
1
0
Order By: Relevance
“…In addition, their report indicated that most tumors were grade II or III, findings that were similar to those of our study. Furthermore, other studies observed the highest prevalence of BRCA1 mutant tumors in triple-negative breast cancer patients [ 22 , 23 ] similar to our findings. Age at diagnosis among the participants in this study was another important factor to note.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, their report indicated that most tumors were grade II or III, findings that were similar to those of our study. Furthermore, other studies observed the highest prevalence of BRCA1 mutant tumors in triple-negative breast cancer patients [ 22 , 23 ] similar to our findings. Age at diagnosis among the participants in this study was another important factor to note.…”
Section: Discussionsupporting
confidence: 92%
“…These findings are similar to those of Rajagopal et al . 2022 [ 22 ]. In addition, their report indicated that most tumors were grade II or III, findings that were similar to those of our study.…”
Section: Discussionmentioning
confidence: 99%
“…The LAR phenotype displays a high expression of AR and could act as a potential target in TNBCs. Mutations in the BRCA genes are also found to be frequently associated with advanced disease in TNBCs, especially among early on-set patients, and the prevalence of these mutations are typically higher ranging in our study from 20% and 26.6% for BRCA1 and BRCA2, respectively [50,51]. Apart from these driver mutations, our data reveals mutations in SLC7A8 (27%; 4/15), AMOT (20%; 3/15), CLEC11A (20%; 3/15), and ECHDC1 (13%; 2/15) genes with a q value of ≤ 0.1.…”
Section: Discussionsupporting
confidence: 49%